EpiMetal: an open-source graphical web browser tool for easy statistical analyses in epidemiology and metabolomics. - Ekholm, Jussi; Ohukainen, Pauli; Kangas, Antti J; Kettunen, Johannes; Wang, Qin; Karsikas, Mari; Khan, Anmar A; Kingwell, Bronwyn A; Kähönen, Mika; Lehtimäki, Terho; Raitakari, Olli T; Järvelin, Marjo-Riitta; et al. (International Journal of Epidemiology, 2020)
Motivation: An intuitive graphical interface that allows statistical analyses and visualizations of extensive data without any knowledge of dedicated statistical software or programming.Implementation: EpiMetal is a single-page web application written in JavaScript, to be used via a modern desktop web browser.General Features: Standard epidemiological analyses and self-organizing maps for data-driven metabolic profiling are included. Multiple extensive datasets with an arbitrary number of continuous and category variables can be integrated with the software. Any snapshot of the analyses can be saved and shared with others via a www-link. We demonstrate the usage of EpiMetal using pilot data with over 500 quantitative molecular measures for each sample as well as in two large-scale epidemiological cohorts (N >10 000).Availability: The software usage exemplar and the pilot data are open access online at [http://EpiMetal.computationalmedicine.fi]. MIT licensed source code is available at the Github repository at [https://github.com/amergin/epimetal].